The Vienna Circle and Logical Empiricism
XXIII, 427 p. 6 illus.
Keywords: The Vienna Circle and Logical Empiricism is for scholars, researchers and students in history and philosophy of science focusing on Logical Empiricism and analytic philosophy (of science). This volume features recent work from international research and historiography on the Vienna Circle and Logical Empiricism and their influence. It is unique in that it: -provides historical and systematic research; -deals with the influence and impact of the Vienna Circle/Logical Empiricism on today's philosophy of science; -explores the intellectual context of this scientific philosophy; -unites contributions by renowned scholars and a younger generation of philosophers; -focuses on main figures and peripheral adherents; -features crucial issues of Logical Empiricism; -documents the activities of the Vienna Circle Institute; -includes reviews on related topics.